Charting diversity and change in IS publications: A tri-continental journal analysis - Keller, Susan; Coulthard, Darryl (Australasian Journal of Information Systems, 2013)
The past decade has seen enormous changes in the availability, use, and application of information systems. Information systems are no longer the preserve of business and the corporation but have become a routine part of everyday life. The purpose of this paper is to explore the extent to which the increased diversity in application and use of information systems in the past decade has been reflected in increased diversity of the publications of three key journals of three continents – North America, Europe, and Australasia. The paper contributes to the debate on research diversity in Information Systems in three ways. Firstly, it describes four key underpinning dimensions for understanding Information Systems (IS) research diversity in the information age. Secondly, it details the results of a content analysis which examines the trends in research and methodological diversity within the journals MIS Quarterly (MISQ), European Journal of Information Systems (EJIS) and the Australasian Journal of Information Systems (AJIS) during the years 2001-2010. Finally, the paper reflects on diversity within these journals and discusses the findings in relation to both exogenous and endogenous pressures on the discipline more broadly.